Dynamic hysteresis modelling of ferromagnetic heisenberg films using mean-field and Fourier analysis - Yongyut Laosiritaworn (2018)
© 2015 Taylor & Francis Group, London. In this work, the hysteresis behavior of the Heisenberg films was modelled using mean-field and Fourier analysis. The mean-field technique was used to investigate the dynamic of Heisenberg magnetization as function of magnetic field parameters, the system temperature, and the films thickness. The dynamic critical temperature which classifies symmetric and asymmetric hysteresis behavior was extracted from the period average magnetization. The dynamic critical temperature was then used to construct the dynamic phase diagram, where the phase boundaries in the diagram can be used to instruct how to vary external perturbation while the hysteresis shape is still preserved. Subsequently, the periodic magnetization signal of the hysteresis was investigation using the Fourier transformation analysis. The first few harmonics were found to have major influences on the overall hysteresis phenomena where hysteresis properties relate to these important harmonics was also established. Discussion on both the dynamic phase diagram and the relationship formalism between the hysteresis properties and the Fourier harmonics were given. Good agreement with previous investigation on other spin models was also found, which support the trustworthiness of this work.